Rootstock influencing the quality and biogenic amines content on Syrah tropical wines - Resende Nassur, Rita de Cássia Mirela; Pereira, Giuliano Elias; Glória, Maria Beatriz Abreu; Lima, Luiz Carlos Oliveira (Comunicata Scientiae, 2018)
The São Francisco Valley, in Brazil, is a region with harvest of grapes more than once a year due to the peculiar climate condition, being important to evaluate new agronomic variables for the vines and elucidade its influence on wine quality and nutritional compounds. Syrah vines grafted on different rootstocks (IAC-313 and Paulsen 1103) were cultivated in semi-arid conditions in Petrolina, PE, Brazil, and the quality of the wine was evaluated for color, sugars, acidity, phenolic compounds, antioxidant activity and the presence and contents of eight biogenic amines by HPLC (putrescine (PUT) dihydrochloride, spermidine (SPD) trihydrochloride, spermine (SPM) tetrahydrochloride, agmatine (AGM) sulfate, cadaverine (CAD) dihydrochloride, serotonine (SRT) hydrochloride, histamine (HIM) dihydrochloride, tyramine (TYM), tryptamine (TRM) and 2-phenylethylamine (PHM) dihydrochloride). For total sugars, color and antocyanins content in the evaluated wines, no effect from the rootstock was observed. For the wine produced with grapes from Syrah wines grafted on Paulsen 1103 rootstock, was observed the presence of putrescine, agmatine and phenylethylamine with the contents of 8.04, 0.15 and 0.22 µg mL-¹, respectively. The use of the rootstock IAC-313 on Syrah vines at the São Francisco Valley semi-arid conditions, Brazil, resulted in wines with a statistical lower pH and soluble solid contents and higher antioxidant activity and phenolic contents, with only the presence of putrescine of the studied biogenic amines.